Magnetic susceptibility of some Lesser Himalayan rocks in central Nepal - Gautam, Pitambar; Ulak, Prakash Das; Gyawali, Baburam; Bhandari, Sudarshan (Journal of Nepal Geological Society, 2011)
Available with full text.